Receptor‐interacting protein kinase 3 mediates macrophage/monocyte activation in autoimmune hepatitis and regulates interleukin‐6 production. Issue 5 (1st June 2018) - Zhang, Jun; Guo, Liping; Liu, Mengjing; Jing, Yang; Zhou, Simin; Li, Hongxia; Li, Yanni; Zhao, Jingwen; Zhao, Xingliang; Karunaratna, Nathasha; Jiang, Kui; Zhou, Lu; et al.
Abstract : Background: The mechanisms of macrophages/monocytes in autoimmune hepatitis (AIH) remain unclear. We investigated the role of receptor‐interacting protein kinase 3 (RIP3), a key inflammatory signal adapter, in macrophage/monocyte activation in AIH. Methods: Liver tissues and monocytes from patients were collected to evaluate the relationship between macrophage activation and RIP3 by double‐immunofluorescence and Western blotting. RAW264.7 macrophages were used to study the regulation of RIP3 signaling on inflammatory cytokines. Results: Compared to the hepatic cyst, the majority of accumulated macrophages expressed RIP3 in AIH liver tissues. Moreover, RIP3 expression of monocytes was correlated with the levels of serum hepatic enzyme in AIH. Furthermore, RIP3 signaling was activated by lipopolysaccharide in RAW264.7 macrophages, which was accompanied with upregulated interleukin (IL)‐1β, IL‐6, and IL‐10 and downregulated IL‐4 and transforming growth factor‐β. Notably, necrostatin‐1, the specific inhibitor of the RIP3 signaling pathway, and 6‐thioguanine (6‐TG), the active metabolite of azathioprine, predominantly reduced IL‐6 production compared to other cytokines. Moreover, the gene level of IL‐6 was dramatically increased in AIH liver tissues. Conclusions: RIP3 signaling is involved in macrophage/monocyte activation in AIH and mediates IL‐6 production, and is a novel molecular mechanism of 6‐TG, indicating that it might be a promising therapeutic target for AIH treatment.